TJNPR 2021
DOI: 10.26538/tjnpr/v5i7.15
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Prebiotic Properties of the Yam Bean (Pachyrhizus erosus (L.) Urban) Tuber Extract

Abstract: Mexican yam bean or Jicama (Pachyrhizus erosus (L.) Urban), Fabaceae family is widely cultivated in several tropical countries in Central America, Western Africa and Southeast Asia. Its edible tuberous root is generally consumed as fresh fruit in Thailand especially in the Northeast of the country. The plant of yam bean can be cultivated simply even in the relative drought area with a growth cycle of approximately 6-8 months. 1 It was reported that the tuber of yam bean contained a high level of water with sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Jicama root studies have been reported by different authors, citing results about their nutraceutical properties (Buckman et al.,2018; González et al., 2018; Khalid & Wan, 2015), including prebiotics (Pulbutr et al., 2021) and dietary fiber (Santoso et al., 2021). For example, a study carried out in murine models regarding the hypoglycemic effect of jicama aqueous extract showed a decrement in blood glucose levels and body weight (Park et al., 2016; Santoso et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jicama root studies have been reported by different authors, citing results about their nutraceutical properties (Buckman et al.,2018; González et al., 2018; Khalid & Wan, 2015), including prebiotics (Pulbutr et al., 2021) and dietary fiber (Santoso et al., 2021). For example, a study carried out in murine models regarding the hypoglycemic effect of jicama aqueous extract showed a decrement in blood glucose levels and body weight (Park et al., 2016; Santoso et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(2021) demonstrated that jicama root extract (soluble fiber) could activate the adaptive immune response by improving the production of cytokines and immunoglobulins (IL‐6, IL‐10, TNF‐a, IgA and IgG) by B cells, while Pulbutr et al. (2021) established that yam bean tuber extract, used as a prebiotic, enhanced the growth of Lactobacillus L. plantarum . In 2020 and 2021, Santoso et al reported that jicama fiber prevents type 2 diabetes mellitus, considering it as a reliable supplement for counteracting the development of this disease.…”
Section: Introductionmentioning
confidence: 99%